2015
DOI: 10.5539/ass.v11n12215
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Global Food Prices to Domestic Prices: Evidence from Sri Lanka

Abstract: Food prices have been increasing sharply since 2003. In the globalized world, the transmission of global food price increases to domestic market determines the decision of economic agents and policy makers of a domestic economy. The recent growth of global food prices affects the welfare of poor consumers and producers. In Sri Lanka, large segment of the population spends more than 50 percent of their income on food. Thus, this study investigates and assesses how international food price surge affects domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…It suggests that a 1% surge in global food price upsurges food price inflation by 0.13%. This result is consistent with Selliah et al [41] for Sri Lanka, Holtemöller and Mallick [17] for India, and Huria and Pathania [18] for India. However, Rajmal and Mishra [37] and Baltzer [4] pointed out a limited transmission of prices from international food prices to domestic prices in India.…”
Section: Results Of Long-run and Short-run Estimatessupporting
confidence: 92%
See 1 more Smart Citation
“…It suggests that a 1% surge in global food price upsurges food price inflation by 0.13%. This result is consistent with Selliah et al [41] for Sri Lanka, Holtemöller and Mallick [17] for India, and Huria and Pathania [18] for India. However, Rajmal and Mishra [37] and Baltzer [4] pointed out a limited transmission of prices from international food prices to domestic prices in India.…”
Section: Results Of Long-run and Short-run Estimatessupporting
confidence: 92%
“…Lee and Park [27] confirmed that the lagged values of global food price inflation are positively impacted food price inflation in 72 countries. Selliah et al [41] revealed that an increase in global food price increases domestic food prices in both the short and long run in Sri Lanka. Similarly, Holtemöller and Mallick [17], Bhattacharya and Sen Gupta [6], and Huria and Pathania [18] also documented that global food price shocks have a significant and positive inflationary trend on food inflation in India.…”
Section: Global Food Price and Food Price Inflationmentioning
confidence: 99%
“…price cause another price to change. The mechanism of transmission of global food prices is a way in which changes in food prices affect economic activity and inflation in several ways(Selliah et al 2015).Price transmission is differentiated into spatial price transmission and vertical price transmission. Meyer andTaubadel (2004) explained that spatial price transmission occured when changes in product prices at a level are transmitted to product prices at the same level in the market chain but at different locations.Then, Taubadel (1998) explained that vertical price transmission is the response of prices at a level to changes in prices at other levels in the market chain, both changes in the form of price increasing or price decreasing Vavra and Goodwin (2005).…”
mentioning
confidence: 99%